Embodiment, Somatics and Dance: some possible links - Souza, Elisa Teixeira de (Revista Brasileira de Estudos da Presença, 2020)
This article´s first objective is to approach the fundamentals of the embodied mind theory by George Lakoff and Mark Johnson to discuss the idea of cellular consciousness from the perspective of neurobiology. We also discuss the field of Somatics and its potential applications on dance, highlighting the possible links between somatization and embodiment.